The intention of utilization and experience toward traditional Chinese medicine among breast cancer patients in the early and late stages: a qualitative study - Kai-wei Chen; Kuo-piao Chung; Chung-hua Hsu (BMC, 2023)
Abstract Background In Taiwan, breast cancer patients usually take conventional medicine and traditional Chinese medicine simultaneously. The utilization of traditional Chinese medicine among breast cancer patients at various stages has not been examined. This study aims to compare the intention of utilization and experience toward traditional Chinese medicine among early- and late-stage breast cancer patients. Method This qualitative research collected data from breast cancer patients through focus groups interview by convenience sampling. Conducted in 2 branches of Taipei City Hospital, a public hospital managed by the Taipei City government. Breast cancer patients > 20 years old and had used TCM for breast cancer therapy for at least 3 months were included in the interview. A semi-structured interview guide was adopted in each focus group interview. In the following data analysis, stages I and II were considered early-stage, and stages III and IV were late-stage. For analyzing the data and reporting the results, we used qualitative content analysis as the approach for data analysis, assisted by NVivo 12. Categories and subcategories were identified through content analysis. Results Twelve and seven early- and late-stage breast cancer patients were included in this study, respectively. The side effects were the main intention of utilizing traditional Chinese medicine. Improving side effects and constitution was the main benefit for patients in both stages. Additionally, early-stage breast cancer patients used traditional Chinese medicine to prevent recurrence or metastasis. Late-stage breast cancer patients responded more frequently to the use of traditional Chinese medicine due to the side effects of western medicine. However, some of their symptoms were not fully relieved. Conclusions Breast cancer staging may influence the intention and utilization of traditional Chinese medicine. Health policymakers should consider the results of this research and the evidence-based illustrations to establish guidelines for integrating traditional Chinese medicine among various stages of breast cancer to improve the outcome and quality of care for cancer patients.